Unveiling the effect of vacancy defects on structural, mechanical, electronic and diffusion properties of copper (I) iodide. (May 2022) - Thomas, Siby; Hildreth, Owen; Asle Zaeem, Mohsen
Abstract: Effects of vacancy defects on formation energies, mechanical stability, electronic properties and diffusion coefficients in copper (I) iodide (CuI) are investigated by first-principles calculations. A temperature-dependent behavior for vacancy formation energy is observed that is explained by the anharmonicity of lattice vibrations at high temperatures. Both Cu and I vacancy defects enhance the electronic conductivity. Cu diffusion is more predominant, because CuI has a less stable structure in the presence of Cu vacancy and atomic bonds of CuI also possess the least stability with Cu vacancies. This study found that the diffusivity increases with an increase of defect concentration and temperature, and Cu diffusion is dominant in CuI regardless of the type of the defect or temperature. Graphical abstract: Image, graphical abstract